2018
DOI: 10.1039/c7lc00832e
|View full text |Cite
|
Sign up to set email alerts
|

A deep conical agarose microwell array for adhesion independent three-dimensional cell culture and dynamic volume measurement

Abstract: Miniaturised conical measures for cell aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 52 publications
1
79
0
Order By: Relevance
“…This method allows for monitoring of dose-dependent effects of combinatorial treatments using cell aggregate volumes as the read out [37]. The presence of A37 alone at higher concentrations (20 μM and 40 μM) lowers cell aggregate volume.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method allows for monitoring of dose-dependent effects of combinatorial treatments using cell aggregate volumes as the read out [37]. The presence of A37 alone at higher concentrations (20 μM and 40 μM) lowers cell aggregate volume.…”
Section: Resultsmentioning
confidence: 99%
“…For 3D experiments, MiaPaCa-2 cells were seeded in conical agarose microwell array (CAMA) to form non-spheroidal cell aggregates as previously described [37]. Briefly, 1000 cells were seeded into each microwell of these CAMA plates, cultured for 48 hours and treated with increasing concentrations (10 μM, 20 μM, and 40 μM) of ALDH1A1 inhibitor A37.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we used a customized 3D in vitro model [53] to isolate EVs released by cell aggregates from two gastric cancer (GC) cell lines. For this purpose, we used a customized 3D in vitro model [53] to isolate EVs released by cell aggregates from two gastric cancer (GC) cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Similar morphology of the colonies was observed in a conventional soft agar assay (Figure B, upper panel); quantitative analysis revealed that Tspan8 overexpression causes a strong reduction of the colony number (Figure B, bottom panel), indicating diminished resistance to anoikis by the MTPa‐Tspan8 cells. Using recently characterised agarose microwell arrays , we tested cell proliferation and observed that, in contrast to 2D, the Tspan8 proliferation‐supporting effect was attenuated in a 3D environment (Figure C).…”
Section: Resultsmentioning
confidence: 99%